Developing academic leadership for transforming higher education Institution of India - Vyas, Parimal and Pandya, Kiran (University News)
Higher education is the cornerstone of economic development, playing a crucial rule in fostering sustainable growth. Academic leadership plays a very crucial role in impacting the education system, where institutions of higher learning are tasked with the dual responsibility of presenting ancient knowledge traditions while embracing modern academic practices as envisioned in national education policy (NEP) 2020. Reproduced